Intersubband optical absorption between multi energy levels of electrons in InGaN/GaN spherical core-shell quantum dots. (February 2017) - Liu, W.H.; Qu, Y.; Ban, S.L.
Abstract: The intersubband optical absorption between multi energy levels of electrons in Inx Ga1-x N/GaN spherical core-shell quantum dots (CSQDs) and ternary mixed crystal and size effects have been investigated by using the principle of density matrix. Electronic eigenstates under the effect of built-in electric field (BEF) have been calculated by a finite element method. The results show that optical absorption between intersubbands with main quantum numbers n = 1 and n = 2 are as important as that between ones with n = 1 and different angular quantum numbers when the BEF is taken into account. In consideration of BEF, the saturation of total optical absorption coefficients (ACs) and secondary peaks of refractive index changes (RICs) appear when incident light intensity I surpasses a certain value. For a given I, the maximum ACs and zero RICs positions in Inx Ga1-x N/GaN CSQDs with a fixed shell size have a blue-shift when x increases or the core Inx Ga1-x N radius R 1 decreases from 5 nm. However, when R 1 > 5 nm, ACs and RICs tend to be stable. The results indicate that effective adjustment of ACs and RICs in CSQDs with BEFs by size is in a limited scale range. The saturation of ACs or secondary peaks of RICs appear more likely in CSQDs with smaller x or larger R 1 . These results are expected to be helpful both in the further theoretical and experimental study on optic devices consisting of CSQDs. Highlights: Based on the finite element method, the electronic states are calculeted in consideration of built-in electric field (BEF). Under the BEF, the optical absorption between intersubbands with main quantum numbers n = 1 and n = 2 is as important as that between ones with n = 1. Size and ternary component can be used to modify the optical absorption coefficients and refractive index changes.